2013
DOI: 10.1186/2191-0855-3-42
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of C6 and C5 sugars in undetoxified wet exploded bagasse hydrolysates using Scheffersomyces (Pichia) stipitis CBS6054

Abstract: Sugarcane bagasse is a potential feedstock for cellulosic ethanol production, rich in both glucan and xylan. This stresses the importance of utilizing both C6 and C5 sugars for conversion into ethanol in order to improve the process economics. During processing of the hydrolysate degradation products such as acetate, 5-hydroxymethylfurfural (HMF) and furfural are formed, which are known to inhibit microbial growth at higher concentrations. In the current study, conversion of both glucose and xylose sugars into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Dilute acid saccharification, however, may lead to the formation of fermentation-inhibitory byproducts due to the high acid concentration to biomass ratio (Girio et al, 2010;Moxley and Zhang, 2007). Dilute acid saccharification products from lignocellulosic biomass contain several fermentation inhibitors like formic acid or hydroxymethylfurfural, and fermentative yeast did not completely consume sugars from the saccharification broth (Wikandari et al, 2010;Biswas et al, 2013). In contrast to lignocellulosic biomass, simple SHF process achieved an ethanol yield of 79.3% from the diluted acid saccharification broth of the lipid-extracted residual biomass of Chlorella sp.…”
Section: Bioethanol Fermentation Using Saccharification Broth Of Lipimentioning
confidence: 98%
“…Dilute acid saccharification, however, may lead to the formation of fermentation-inhibitory byproducts due to the high acid concentration to biomass ratio (Girio et al, 2010;Moxley and Zhang, 2007). Dilute acid saccharification products from lignocellulosic biomass contain several fermentation inhibitors like formic acid or hydroxymethylfurfural, and fermentative yeast did not completely consume sugars from the saccharification broth (Wikandari et al, 2010;Biswas et al, 2013). In contrast to lignocellulosic biomass, simple SHF process achieved an ethanol yield of 79.3% from the diluted acid saccharification broth of the lipid-extracted residual biomass of Chlorella sp.…”
Section: Bioethanol Fermentation Using Saccharification Broth Of Lipimentioning
confidence: 98%
“…New pretreatment methods, enzymes, and yeasts also open the option of ethanol fermentation of lignocellulosic biomass. 28,29 Besides the more diverse energy carriers produced, these technologies also provide increased recovery of nutrients 30 and may alleviate the need for compensatory fertilizing on cereal fields. In some of these technologies (e.g., anaerobic digestion), the straw in fact can be used twice; first as animal bedding in deep straw beds, and then as an energy resource in the digestion chamber.…”
Section: Box 1 Emerging Conversion Technologies For Straw Fuelmentioning
confidence: 99%
“…It was demonstrated that the use of oxygen during pretreatment enhances the performances and allow for lower temperatures during the pretreatment process, reduces the heat requirement due to the production of heat in the process and minimize the formation of degradation products . Further, unlike other pretreatment methods that use hazardous chemicals, the pretreated biomass materials using WEx can be directly used as substrate for subsequent enzymatic hydrolysis and fermentation without any detoxification (Biswas et al, 2013). The process without such chemical requirement allows for large-scale implementation without having additional chemical recovery step(s) and/or need for chemical waste disposal leading to extra cost.…”
Section: Introductionmentioning
confidence: 97%